Food Availability of Wetland Farmers: A Socioeconomic Analysis in Hulu Sungai Utara, South Kalimantan - Ahmad Suhaimi; Rum Van Royensyah; Azwar Saihani; Dewi Susanti; Ulpa Ulpa (CV Projurnal Mitra Publikasi, 2025)
Household food availability is one of the main pillars of food security, which is greatly influenced by socioeconomic conditions, especially in wetland agricultural areas with ecological and infrastructure limitations. This study examines household food availability levels and identifies key socioeconomic determinants among farming households in Karias Dalam Village, Banjang Subdistrict, Hulu Sungai Utara Regency, an area characterized by wetland agroecosystems with significant ecological and infrastructural limitations. Employing a cross-sectional analytical survey design, data were collected from 42 farming households selected through simple random sampling from a population of 280 households. Quantitative descriptive analysis and multiple linear regression (α = 5%) were applied to assess food availability measured in kcal/capita/day and its relationship with household income, mothers’ nutritional knowledge, and family size. The findings reveal that farming households operate at moderate food availability levels, averaging 1,462 kcal/capita/day which is a substantial deficit of 39% below the national recommended dietary allowance of 2,400 kcal. Multiple linear regression analysis demonstrates that household income, mothers’ nutritional knowledge, and family size simultaneously exert significant effects on food availability (F = 10.847, p < 0.001), with these factors collectively explaining 46.1% of the variance (R² = 0.461). Specifically, income and nutritional knowledge demonstrate positive associations, while larger family size negatively impacts per capita food availability. These results underscore the urgent need for integrated policy interventions combining income diversification, maternal nutrition education, and family planning support to enhance food security in wetland agricultural communities. The study contributes empirical evidence for context-specific food security strategies in Indonesia’s marginalized wetland ecosystems.